2020
DOI: 10.1038/s41598-020-62196-4
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Cell Wall and Methyl-β–Cyclodextrin Synergistically Enhance Paclitaxel Biosynthesis and Secretion in Corylus avellana Cell Suspension Culture

Abstract: paclitaxel is the top-selling chemotherapeutic drug used for the treatment of lung, ovarian and breast cancer as well as Kaposi's sarcoma. cell suspension culture (cSc) of Corylus avellana has been addressed as a promising alternative for producing paclitaxel. in this study, endophytic fungus strain Yef 33 was isolated from Taxus baccata and identified as Coniothyrium palmarum. The effects of the elicitors derived from this fungus including cell extract, culture filtrate and cell wall (CW) and also chitin, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Based on our previous studies (Salehi et al, 2019b;Salehi et al, 2019c;Farhadi et al, 2020), three concentrations [2.5, 5, and 10% (v/v)] of fungal elicitors "CE:CF (100:0, 75:25, 50:50, 25:75, 0:100 v/v)" and also mid (day 13) and late (day 17) log phase of C. avellana cell cultures were selected for adding fungal elicitors. Control received an equal volume of water (for CE)/ PDB (for CF).…”
Section: Elicitation Of C Avellana Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Based on our previous studies (Salehi et al, 2019b;Salehi et al, 2019c;Farhadi et al, 2020), three concentrations [2.5, 5, and 10% (v/v)] of fungal elicitors "CE:CF (100:0, 75:25, 50:50, 25:75, 0:100 v/v)" and also mid (day 13) and late (day 17) log phase of C. avellana cell cultures were selected for adding fungal elicitors. Control received an equal volume of water (for CE)/ PDB (for CF).…”
Section: Elicitation Of C Avellana Cell Culturementioning
confidence: 99%
“…Previous studies (Salehi et al, 2019b;Salehi et al, 2019c;Farhadi et al, 2020;Salehi et al, 2020) demonstrated the positive influences of cell extract (CE) and culture filtrate (CF) of endophytic fungi on paclitaxel biosynthesis in cell suspension culture (CSC) of C. avellana. Fungal elicitor type, concentration and adding time, and also exposure time of cell culture (CSC harvesting time) should be optimized to achieve the maximum biosynthesis of paclitaxel in C. avellana CSC (Salehi et al, 2019b;Salehi et al, 2019c;Farhadi et al, 2020;Salehi et al, 2020). Precise analysis of the effects of these factors and their optimal selection would pave the way for the commercialization of bioprocessing C. avellana cells toward paclitaxel mass production.…”
Section: Introductionmentioning
confidence: 99%
“…Since Taxus trees are slow-growing and harvesting the bark is destructive [ 5 ], thus the continuous harvest of native plant bark for commercial production of paclitaxel was untenable. Nowadays, plant cell factories offer a promising and environment-friendly approach for large-scale paclitaxel production [ 6 10 ]. The rising demand for paclitaxel, and Taxus recalcitrant behavior under in vitro conditions have caused extensive efforts toward finding alternatives for producing this invaluable secondary metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…avellana is a dicotyledonous plant, possibly C . avellana response to genetic manipulation by Agrobacterium is more promising than that of Taxus [ 7 10 ]. Obtaining high-producing in vitro cultures is a key step for producing secondary metabolites through plant cell culture (PCC) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation